Volumetrics and fit assessments for donor to recipient size matching in pediatric heart transplantation: Is it time for a new paradigm?. Issue 5 (23rd March 2020) - Ploutz, Michelle S.; Plasencia, Jonathan D.; Mirea, Lucia; Pophal, Stephen G.; Velez, Daniel A.; Zangwill, Steven D.
Abstract: Pediatric heart transplant patients face the highest waitlist mortality in solid organ transplantation. Given the relatively fixed number of donor organs becoming available each year, improving donor organ utilization could potentially have significant impact on reducing waitlist mortality. Donor to recipient weight ratio has historically been used to identify suitable donors; however, this method does not take into account the potential for significant variance in heart size due to complex congenital heart disease or underlying cardiomyopathy. We believe, based on our experience to date, that donor matching based upon weight ratios should be augmented by improved methodologies that provide a more accurate assessment of heart volumes. Herein we describe the rationale for these methodologies and our single‐center experience using volumetrics as an alternative for donor fit assessments.